Current status and development trend of photovoltaic electrolysis hydrogen production technology - Li Yansha (E3S Web of Conferences)
With the increasing global demand for addressing climate change and energy transformation, photovoltaic electrolysis hydrogen production technology has received widespread attention as a viable green energy solution. This paper reviews the basic principles, technical status, key challenges and future development directions of photovoltaic electrolysis hydrogen production technology, focusing on the coupling mechanism of water electrolysis technology and photovoltaic power generation and its application potential in the hydrogen energy industry. At the same time, this paper analyzes the economic feasibility of photovoltaic hydrogen production and looks forward to future technological innovation directions. With the continuous decline in the cost of photovoltaic power generation and the continuous advancement of electrolysis hydrogen production technology, photovoltaic hydrogen production technology will become an important pillar of the world’s new energy industry and provide important support for the transformation of the global energy structure.